Link between bilaterality and type 2 inflammation in respiratory epithelial adenomatoid hamartomas: A two-center retrospective cohort study - Yujin Heo; Sang Duk Hong; Hyo Yeol Kim; Gwanghui Ryu; Kyung Won Kwon; Yong Gi Jung (PLoS ONE, 2025)
Background Sinonasal respiratory epithelial adenomatoid hamartomas (REAH) are rare benign lesions with diverse clinical characteristics. Their pathogenesis remains unclear, with hypotheses suggesting either an inflammatory process or neoplastic origin. Despite their clinical heterogeneity, a formal subtype classification is lacking. This study analyzes the clinical features of surgically treated sinonasal REAH and investigates disease characteristics based on bilaterality, particularly in relation to type 2 chronic rhinosinusitis. Methods This retrospective analysis included patients with REAH who underwent endoscopic surgery and received pathological confirmation between November 2008 and November 2023. Demographic data, including asthma history, prior sinus surgeries, serum eosinophil levels, and the Japanese Epidemiological Survey of Refractory Eosinophilic Chronic Rhinosinusitis (JESREC) score, were analyzed in relation to REAH bilaterality. Results Among 21 patients (17 males, 4 females; mean age 46.5 years), 11 cases (52.4%) exhibited bilateral origins (REAH_bi) in the superior nasal septum and olfactory cleft, while 10 cases (47.6%) presented as isolated unilateral lesions (REAH_uni). REAH_bi was significantly associated with asthma (p = 0.012), prior sinus surgery (p = 0.002), and inflammatory polyposis (p = 0.002) compared to REAH_uni. Elevated preoperative serum eosinophil levels and JESREC scores were also noted in REAH_bi cases (p = 0.021 and <0.001, respectively). Neither group showed recurrence during a mean follow-up of 11.91 months. Conclusion Bilaterally originating REAH in the superior nasal septum and olfactory cleft demonstrates pronounced type 2 inflammatory characteristics, suggesting potential differences in pathogenesis compared to unilateral REAH. These findings underscore the need for further investigation into REAH pathophysiology and emphasize the importance of bilaterality in clinical assessment.